STRATEGI PENGGALIAN DANA PUNIA PADA UMAT HINDU KOTA PALU DALAM PEMBANGUNAN CANDI KURUNG PURA AGUNG WANA KERTHA JAGATNATHA SULAWESI TENGAH (PERPEKSTIF PENDIDIKAN AGAMA HINDU) - Ni Ketut Ratini (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
The construction of the Great Wung Kertha Jagatnatha Kurung Pura Temple, CentralSulawesi, is the result of world funds from Hindus in Central Sulawesi in general and Hindus inPalu City in particular, which costs Rp. 1.1 billion. The construction committee has managed tocollect this huge fund. This is quite fantastic considering that today humanity tends to be morematerialistic, but it is evident that the committee with various strategies managed to raise fundsfor the construction of the brackets. This research uses Management Function Theory andStructural Functionalism theory to dissect existing problems. The approach used is a qualitativeapproach located in the City of Palu. The technique of determining the informant is done byusing purposive sampling method, while the data collection method consists of interview method,documentation method and literature study. From the results of the research and discussion, itcan be concluded that: 1) Strategy for Extracting the World Fund for Hindus in Palu City in theConstruction of Kurung Pura Agung Wana Temple Kerta Jagat Natha in Central Sulawesi,namely Circulating List, Through Announcements on Worship at the Temple, PHDI NightGathering, Submission of Development Proposals To Institutions, Dana Punia Banjar Policy,Bazaar and Prize World Funds; 2) Constraints encountered in the Strategy for Extracting theWorld Fund to Hindu City of Palu in the Construction of the Kurung Pura Agung Wana TempleKerta Jagat Natha in Central Sulawesi includes: Not the Uneven Economy of Hindus in PaluCity; Late Entry of Punia Umat; and the Coupon Distribution Constraints, 3) the developmentcommittee has clarified the outstanding coupons by conducting intensive communication andsocialization with existing community leaders and donors, so that it will not be prolonged andhampers the development committee program.